Sequential recruitment of body fluid spaces for increasing volumes of crystalloid fluid - Hahn, Robert G. (Frontiers in Physiology, 2024)
Introduction. The interstitial space harbours two fluid compartments linked serially to the plasma. This study explores conditions that lead to fluid accumulation in the most secluded compartment, termed the "third space".Retrospective data was collected from 326 experiments in which intravenous crystalloid fluid was administered to conscious volunteers as well as a small group of anaesthetized patients. The urinary excretion and plasma dilution derived from haemoglobin served as input variables in nine population volume kinetic analyses representing subtly different settings.Results. An infusion of 250-500 mL of Ringer's solution expanded only the central fluid space (plasma), whereas the infusion of 500-1,000 mL extended into a rapidly exchanging interstitial fluid space. When more than 1 litre was infused over 30 min, it was distributed across plasma and both interstitial fluid compartments. The remote space, characterized by slow turnover, abruptly accommodated fluid upon accumulation of 700-800 mL in the rapidly exchanging space, equivalent to an 11-13% volume increase. However, larger expansion was necessary to trigger this event in a perioperative setting. The plasma half-life of crystalloid fluid was 25 times longer when 2,000-2,700 mL expanded all three fluid compartments compared to when only 250-500 mL expanded the central space (14 h versus 30 min).As the volume of crystalloid fluid increases, it apparently occupies a larger proportion of the interstitial space. When more than 1 L is administered at a high rate, there is expansion of a remote "third space", which considerably extends the intravascular halflife.